2021
DOI: 10.1001/jamacardio.2021.2621
|View full text |Cite|
|
Sign up to set email alerts
|

Contemporaneous Comparison of Outcomes Among Patients Implanted With a Leadless vs Transvenous Single-Chamber Ventricular Pacemaker

Abstract: IMPORTANCEThe safety and efficacy of leadless VVI pacemakers have been demonstrated in multiple clinical trials, but the comparative performance of the device in a large, real-world population has not been examined. OBJECTIVE To compare patient characteristics and complications among patients implanted with leadless VVI and transvenous VVI pacemakers. DESIGN, SETTING, PARTICIPANTS The Longitudinal Coverage With Evidence Development Study on Micra Leadless Pacemakers (Micra CED) is a continuously enrolling obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 17 publications
2
68
1
2
Order By: Relevance
“…The results of this current study build off of recently published results of shorter-term (30-day and 6-month) outcomes of the Micra CED study, 5 which found patients implanted with a leadless VVI pacemaker had higher rates of pericardial effusion and/or perforation, but lower rates of other device-related complications and need for system revisions, with no difference in the adjusted overall rate of acute (30-day) complications. These results are similar to a 2017 review by Tjong and Reddy, 12 which found slightly higher rates of short-term complications in leadless patients.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The results of this current study build off of recently published results of shorter-term (30-day and 6-month) outcomes of the Micra CED study, 5 which found patients implanted with a leadless VVI pacemaker had higher rates of pericardial effusion and/or perforation, but lower rates of other device-related complications and need for system revisions, with no difference in the adjusted overall rate of acute (30-day) complications. These results are similar to a 2017 review by Tjong and Reddy, 12 which found slightly higher rates of short-term complications in leadless patients.…”
Section: Discussionsupporting
confidence: 68%
“…Post-market device data linked to CMS claims data have now served to provide important insight into multiple new device technologies, including transcatheter mitral repair 19 and now leadless VVI pacing. 5 Studies relying solely on CMS FFS claims data cannot supplant a holistic approach to post-market evaluation; however, CMS data can provide essential insights into utilization, safety, and outcomes in general US practice that cannot be provided in a traditional disease-specific registry platform. Notably, the Micra CED study illustrates the feasibility of utilizing real-world data to generate evidence measuring the effectiveness of new technology and can serve as a potential model for coverage of new medical technologies in other healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the rate of cardiac perforation associated with leadless pacing systems has been found to be less than 1% (0.77% in the Micra™ PAR population and 0.8% in the Micra™ CED population, respectively), this rate appears to be higher than that associated with transvenous pacemaker implantation (0.4% in the control group of the Micra™ CED study). 4 In a report of the MAUDE database, three episodes of VF/VF were reported, all in the setting of perforation and effusion. 5 …”
Section: Drs Blank and El-chami Commentmentioning
confidence: 99%